2019
DOI: 10.1080/21548331.2019.1685800
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments of medication dosages in patients with renal impairment in Botswana; findings and implications to improve patient care

Abstract: Background and aims: Medication dosage adjustments for renally impaired patients have not been studied in Botswana. This study was conducted to determine prescribing practices among patients with renal impairment in medical wards to improve future patient care. Methods: We conducted a retrospective study involving medical charts of patients admitted at a tertiary level hospital in Gaborone Botswana. Study participants included all patients admitted between August and October 2016 who were hospitalized for ≥24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Although an eGFR of <59 mL/min/1.73 m 2 was used in their study to define renal impairment compared to eGFR ≤60 mL/min/1.73 m 2 used in our study, the prevalence of renal impairment was less. The definition of renal impairment varies among different information sources [ 10 ]. However, medicine dosing guidelines are typically derived from studies performed in patients with stable, chronic renal insufficiency and the recommendations are extrapolated to seriously ill patients with acutely decreased renal function [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although an eGFR of <59 mL/min/1.73 m 2 was used in their study to define renal impairment compared to eGFR ≤60 mL/min/1.73 m 2 used in our study, the prevalence of renal impairment was less. The definition of renal impairment varies among different information sources [ 10 ]. However, medicine dosing guidelines are typically derived from studies performed in patients with stable, chronic renal insufficiency and the recommendations are extrapolated to seriously ill patients with acutely decreased renal function [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this study to evaluate the appropriateness of medicine dosing adjustment, renal impairment was defined as estimated GFR ≤60 ml/min/1.73 m 2 [ 24 ]. The possible explanation for this discrepancy may be due to the current increasing number of patients visiting hospitals and the prevalence of renal impairment increases in an alarming rate [ 31 ], which is less prevalent than recent study done in Botswana that showed 29% [ 10 ]. This may be attributed to the fact that we used estimated GFR, rather than a SrCrto-defined renal impairment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations